Type II Supernova Spectral Diversity. II. Spectroscopic and Photometric Correlations - Gutiérrez, Claudia P. (2017)
We present an analysis of observed trends and correlations between a large range of spectral and photometric parameters of more than 100 type II supernovae (SNe II), during the photospheric phase. We define a common epoch for all SNe of 50 days post-explosion, where the majority of the sample is likely to be under similar physical conditions. Several correlation matrices are produced to search for interesting trends between more than 30 distinct light-curve and spectral properties that characterize the diversity of SNe II. Overall, SNe with higher expansion velocities are brighter, have more rapidly declining light curves, shorter plateau durations, and higher 56Ni masses. Using a larger sample than previous studies, we argue that "Pd" - the plateau duration from the transition of the initial to "plateau" decline rates to the end of the "plateau" - is a better indicator of the hydrogen envelope mass than the traditionally used optically thick phase duration (OPTd: explosion epoch to end of plateau). This argument is supported by the fact that Pd also correlates with s3, the light-curve decline rate at late times: lower Pd values correlate with larger s3 decline rates. Large s3 decline rates are likely related to lower envelope masses, which enables gamma-ray escape. We also find a significant anticorrelation between Pd and s2 (the plateau decline rate), confirming the long standing hypothesis that faster declining SNe II (SNe IIL) are the result of explosions with lower hydrogen envelope masses and therefore have shorter Pd values.